Analisis Kekuatan Lentur Balok Aplikasi Tulangan Komposit Dengan Perlakuan Bedamutu - Marsudi Marsudi; Martono Martono (Semesta Teknika, 2017)
Concrete has a very high compressive strength, while tensile strength only 10 % from compressive strength. Concrete as building materials have varying prices depending on the quality of the concrete. The use of different concrete quality is expected to reduce production costs with the same strength. Steel concrete is the product can not be update, whose existence will someday be exhausted. To overcome these problems, As a replacement alternative is the use of bamboo reinforcement with wire bendrat that cost cheaper and high strength. In this research steel concrete is replaced the bamboo reinforcement with give bendrat wire is used of a simple concrete beam reinforcement. All beams concrete are given bamboo reinforcement with wire bendrat. The final results of research will known how big and ability beam modification with reinforcement of bamboo petung with the wire bendrat in receive bending style. Slump test, the test result is 7 to 10 cm. From the test results strength urge concrete cubes can be deduced that the average compressive strength of concrete K-150 is 157 kg / cm2 means that the average concrete has a quality K-157, higher than the planning the quality of (K-150) , then to the quality of concrete K-225, the average compressive strength of concrete have the quality of K-229, higher than the plan that is the quality of (K-225). Results of testing the tensile strength of concrete steel Ø 6 mm obtained an average value of 15 kN, whereas tes result for the reinforcement of bamboo petung profile that diprofil with bendrat obtained average value of 12 kN. Flexure testing result revealed that the quality of concrete beam strength of K-225 gained an average of 36.67 kN, while to the quality of K-150 in get strength 27 kN. The modification concrete beam different quality concrete with reinforcement bamboo petung reinforcement with is given bendrat wire is average test results research of 28.33 kN,while for testing concrete beam reinforced steel with different quality, the research result of flexure test give results 36.33 kN.